2021
DOI: 10.1111/1759-7714.13780
|View full text |Cite
|
Sign up to set email alerts
|

In vitro studies of H520 cell cycle and apoptosis by anlotinib combined with radiotherapy

Abstract: Background To study in vitro the effects of anlotinib combined with radiotherapy on the lung cancer H520 cell cycle and apoptosis. Methods The log growth period H520 cells were divided into the control group, anlotinib group (A group), radiotherapy group (RT group) and combined group (A + RT group). Cell cycle and apoptosis were detected by flow cytometry and changes in H520 cell cycle and apoptosis were analyzed in each group. Results Anlotinib was determined to significantly inhibit cell growth in all groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Our study also mentioned that Anlotinib also exhibited great effects on promoting the e cacy of radiotherapy in EC. Consistently, it is noted that in the setting of lung cancer, the synergism of radiotherapy and Anlotinib is more effective to suppress cell proliferation and tumor cell growth than administration of Anlotinib alone [23]. Overall, Anlotinib is a promising drug for managing the process of cancer and improving the survival of cancer patients; moreover, Anlotinib and radiotherapy synergistically function to control tumorigenic activities of malignant cells.…”
Section: Discussionmentioning
confidence: 82%
“…Our study also mentioned that Anlotinib also exhibited great effects on promoting the e cacy of radiotherapy in EC. Consistently, it is noted that in the setting of lung cancer, the synergism of radiotherapy and Anlotinib is more effective to suppress cell proliferation and tumor cell growth than administration of Anlotinib alone [23]. Overall, Anlotinib is a promising drug for managing the process of cancer and improving the survival of cancer patients; moreover, Anlotinib and radiotherapy synergistically function to control tumorigenic activities of malignant cells.…”
Section: Discussionmentioning
confidence: 82%
“…Our study also mentioned that anlotinib also exhibited great effects on promoting the efficacy of radiotherapy in EC. Consistently, it is noted that in the setting of lung cancer, the synergism of radiotherapy and anlotinib is more effective to suppress cell proliferation and tumor cell growth than the administration of anlotinib alone [ 25 ]. Overall, anlotinib is a promising drug for managing the process of cancer and improving the survival of cancer patients; moreover, anlotinib and radiotherapy synergistically function to control the tumorigenic activities of malignant cells.…”
Section: Discussionmentioning
confidence: 94%
“…Anlotinib combined with radiotherapy synergistically inhibits the growth of tumour cells. 24 Cranial radiotherapy can increase the permeability of the BBB, which may increase anlotinib content in brain tissue; thus, the curative effect of cranial radiotherapy combined with anlotinib may be superior to that of cranial radiotherapy alone for NSCLC patients with no specific gene mutation. 25 A previous retrospective study 26 and 2 prospective studies 27 , 28 suggested that anlotinib combined with radiotherapy for BM has satisfactory efficacy with tolerable toxicity.…”
Section: Discussionmentioning
confidence: 99%